Impact of nutrition communication intervention on the quality of mid day meal programme - Sheelakumary J (Department of Agricultural Extension, College of Agriculture, 2012)
The presented study entitled “Impact of nutrition communication intervention on the quality of mid day meal programme” was conducted with the objective of imparting nutrition communication as an intervention programme in order to improve the quality of mid day meals and to assess its impact.